On the reflection of solitary waves from steep slopes - Kotelnikova, A. S.; Nikishov, V. I. (Reports of the National Academy of Sciences of Ukraine, 2015)
The results of experimental investigations of the interaction of surface solitary waves with steep slopes are presented. It is found that the "dispersive tail" is formed during the interaction of a wave with steep slopes. The spectrum of the "tail" (wave train) has a pronounced maximum. The dependences of the spectral maximum frequency on the water depth and the slope angle are analyzed. The features of the formation of a "tail" are discussed.